Implementing the TPACK model to enhance learning outcomes of future biology teachers for the digital era - Rosamsi, Saiman; Nurdiani, Nia (JPBIO (Jurnal Pendidikan Biologi), 2024)
This research is motivated by the rapid development of technology, which has impacted learning in preparing prospective teachers for the digital era. One of the essential competencies required for this preparation is the ability to implement the TPACK model in the learning process to improve the learning outcomes of prospective biology teacher students. This study aims to analyze the effect of implementing the Technological Pedagogical Content Knowledge (TPACK) model on the learning outcomes of prospective biology teacher students in preparing them as educators in the digital era. TPACK is a framework that integrates technology, pedagogy, and content to create more effective and interactive learning experiences. The research method used is quasi-experimental, employing a non-equivalent control group design. The results show a significant improvement in the learning outcomes of students in the experimental group compared to the control group. The implementation of TPACK also enhances students' technological skills, which are crucial for their preparation as teachers in the digital era. This study concludes that the application of TPACK not only has a positive impact on cognitive learning outcomes but also fosters a positive attitude towards the use of technology and improves students' psychomotor skills.